The impact of social media advertising on audience trust and purchase intentions - Quek, Xiao Tong (2024)
This study examines the impact of social media advertising on audience trust and purchase intention among university students. While marketing methods have been developing rapidly in the digital era, brands seek to engage consumers through social media. The present research addresses the dual nature of the relationship between trust of social media advertising by consumers and buying behaviour. Quantitative approach was followed, and the survey questionnaire was shared through Google Forms in a group of participants that included 53. The results stated that the content type, for instance, fashion and lifestyle, encourages more interaction that may affect positive purchase intention. It was observed that reviews, comparison shopping, and local customer feedback are considered to be the major drivers in trusting social media advertising. This will also bring marketers closer to working out an optimal strategy in social media by addressing platform-specific features and regional influences that affect consumer behaviour. It also points to transparency, ethical practices, and localization of marketing efforts as cardinal imperatives in audience trust-building and maintenance.